Contribuições da teoria de Piaget para a formação de professores/Contribution of Piaget's theory to the formation of teachers - Eliane Giachetto Saravali (Universidade Estadual de Campinas, 2004)
O artigo discute a importância do conhecimento e do aprofundamento do referencial construtivista de Jean Piaget e suas principais contribuições para a formação do pedagogo e sua prática docente. Mediante a análise das respostas de estudantes de Pedagogia a um questionário avaliativo, o texto apresenta as percepções dos alunos sobre o estudo continuado da epistemologia genética. The article discusses the importance of the knowledge and of the deepening of Piaget's constructivist referential and his main contributions to the formation of the pedagogue and his teaching practice. According to the analysis of the answers of Pedagogy students to an estimator questionary, the text presents the perceptions of the students about the continual study of the genetic epistemology.